1937
DOI: 10.1002/aja.1000610102
|View full text |Cite
|
Sign up to set email alerts
|

Cytological changes in the rat thyroid following exposure to heat and cold, and their relationship to the physiology of secretion

Abstract: TEN TEXT FIGURES AND OXE PLATE (SIX FIGURES) ISTRODUCTLONThe purpose of this study is to investigate cytological changes in the rat thyroid under corditions of experimental stimulation arid depression. It will be shown that when one compares a series of activated glands with the normal, he can trace the progressive mobilization of certain intra-cellular organoids which probably act collectively to form secretion products. I n the same manner, depression in activity of the gland also causes certain noticeable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1938
1938
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…He demonstrated a second epithelial cell, described as " parafollicular " by virtue of its argyrophilia in material processed by the technique of Cajal. The original observations were confirmed by Nonidez (1932Nonidez ( ,1933, by Raymond (1932), Ohkubo (1934, Vacirca (1936), Baillif (1937), Sunder-Plassmann (1939, Altmann (1940), andSandritter andKlein (1954). More recently the cytology, cytochemistry, and electron microscopy of the parafollicular cells of dog thyroid have been described by Pearse (1966).…”
Section: S Y N O P S I Smentioning
confidence: 80%
See 1 more Smart Citation
“…He demonstrated a second epithelial cell, described as " parafollicular " by virtue of its argyrophilia in material processed by the technique of Cajal. The original observations were confirmed by Nonidez (1932Nonidez ( ,1933, by Raymond (1932), Ohkubo (1934, Vacirca (1936), Baillif (1937), Sunder-Plassmann (1939, Altmann (1940), andSandritter andKlein (1954). More recently the cytology, cytochemistry, and electron microscopy of the parafollicular cells of dog thyroid have been described by Pearse (1966).…”
Section: S Y N O P S I Smentioning
confidence: 80%
“…Since the original discovery of the C cells many hypotheses have been proposed with regard to their nature and function. At one time or another they have been considered as tangential sections of groups of follicular cells (Wilson, 1927;Ludwig, 1953), cells originating from follicular cells (Altmann, 1940;Nonidez, 1932), cells dealing with the neoformation of follicles (wolfler, 1883;Florentin, 1929;Zechel, 1932;Baillif, 1937;Saito & Shibata, 1957), cells belonging to the system of Feyrter (Ponse, 1951), cells migrating to the parathyroid (Getzowa, 1907;Halpenny & Thompson, 1909), cells originating from embryonic structures such as the ultimobranchial body (Godwin, 1937), or thyroglossal duct (Dumont, 1956), neurosecretory cells (Sunder-Plassmann, 1939), and secretory cells (Baber, 1876;Takagi, 1922/23;Nonidez, 1931/2;Ohkubo, 1934;Geraldes Barba, 1944, 1946,1948,1950.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid weight curves of the muskrat, thirteen-lined ground squirrel and the cottontail rabbit are in contrast with the findings of Riddle and , Fisher (1925) that pigeons have an enlargement of the thyroid in the fall and winter. Kenyon (1933) and Baillif (1937) have shown that in the white rat exposure to cold causes an outbreak of activity in the thyroid which is observable in both its histology and weight. This did not seem to show in the seasonal weight picture of the muskrat thyroid.…”
Section: Admentioning
confidence: 43%
“…49 Cold exposure increases the activity of the thyroid gland to produce thyroid hormones. [50][51][52] Thus, elevated thyroid activity may lead to cancer development in the thyroid gland upon cold exposure. Our findings also demonstrate a strong negative correlation between AAT and thyroid-specific CIR data that exists in both male and female populations ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The data for females were also used to compare the counties with the lowest CIR-AAS above and below 36.5°N latitude (25,50,100,200, and 500; Table 4, Figure 2, and Supplementary Figure S8). This analysis also demonstrates that counties located above the 36.5°N have a 0.35-to 0.55fold increase in CIR-AAS (from top 25 to top 500) as compared to the counties located below the 36.5°N.…”
Section: Cancer Incidence Increases In Females Above Latitude 365°nmentioning
confidence: 99%